STRATEGIC MANAGEMENT ACCOUNTING AS A TOOL TO PROMOTE COMPETITIVENESS AND EFFICIENCY OF THE ACTIVITY OF THE ENTERPRISE - N. Kuprina (Ekonomìka Harčovoï Promislovostì, 2017)
Approaches to the definition of essence of strategic management accounting in scientific works of national and foreign scientists are considered. The objective necessity of its application at the enterprises of Ukraine in the current conditions of the state and development of the economy and market relations which requires the expansion of the range of its objects and methods of management accounting are substantiated. The necessity of adaptation of foreign experience of organization and introduction of strategic management accounting, are considered application of methods of its management to national economic and market conditions, taking into account specificity in Ukraine. The place of strategic management accounting as an instrument in the system of management of the efficiency of their activities and competitiveness in the present conditions is given.